2001
DOI: 10.1200/jco.2001.19.3.666
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cystectomy in the Treatment of Invasive Bladder Cancer: Long-Term Results in 1,054 Patients

Abstract: These data from a large group of patients support the aggressive surgical management of invasive bladder cancer. Excellent long-term survival can be achieved with a low incidence of pelvic recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

110
2,169
15
121

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,251 publications
(2,415 citation statements)
references
References 21 publications
110
2,169
15
121
Order By: Relevance
“…Bladder cancer is a major health problem in the United States, causing approximately 14,000 deaths per year. 2 Current chemotherapeutic regimens result in cure in only a small proportion of patients, and responses are not durable. At the current time, to our knowledge there are no real prognostic factors available other than tumor stage and grade, although attempts have been made to identify molecular markers such as p53 and Ki-67.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bladder cancer is a major health problem in the United States, causing approximately 14,000 deaths per year. 2 Current chemotherapeutic regimens result in cure in only a small proportion of patients, and responses are not durable. At the current time, to our knowledge there are no real prognostic factors available other than tumor stage and grade, although attempts have been made to identify molecular markers such as p53 and Ki-67.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent refinement of various therapeutic strategies, including surgery, radiotherapy, chemotherapy, and combination therapy, the 5-year survival rate remains 50% to 60%. 1,2 One of the reasons for poor prognosis is that bladder cancer, being highly invasive, is frequently associated with extensive local invasion or regional lymph node metastasis, even at initial diagnosis. Targeted therapy with growth factor antagonists has not lived up to its promise.…”
mentioning
confidence: 99%
“…In evaluating patients for treatment, patients and physicians commonly focus on tumor characteristics such as grade and stage, which have proven to predict risk of recurrence, progression, metastasis, and death [1,2]. Efforts have been made to improve risk assessment by examining other pathological parameters such as number of lymph nodes [16], depth of tumor invasion [17], and biomarker status [18].…”
Section: Discussionmentioning
confidence: 99%
“…While prognostic factors for cancer in general and bladder cancer specifically traditionally focus on gross and microscopic tumor characteristics [1,2], overall health of patients often impacts survival. Comorbidity is defined as any coexisting disease or condition that may impact diagnosis, treatment, and prognosis for an index disease (in this study, bladder cancer).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term oncological and functional outcomes are still needed though. Large series with long term follow-up in ORC have shown that approximately half of all cystectomy patients experience local recurrence or distant metastatic disease with subsequent mortality [3]. Surgeons should choose their patients early in their RARC learning curve due to concerns for oncologic control and the technically difficult nature of RARC [4,5].…”
Section: Introductionmentioning
confidence: 99%